KIDUNG MONANI DALAM PENGUKURAN KINERJA SOSIAL (STUDI KASUS PT. PRIMA ALAM GEMILANG) - Tenriwaru Tenriwaru; Yunda Dwi Putri Rustam; Muslim Muslim (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2022)
Kidung Monani (Monani Chant) is one of Moronene’s cultures that aims to educate anyone to always taking care of nature as well as local prosperisty. This research is aimed to figure out and analyze the implementation the Kidung Monani philosohpy in measuring social responsibility carried out by PT. Prima Alam Gemilang in Bombana. This research used prime data collected from interviews, observation, documentation; while the secondary data are from the company and journals regarding this matter. Collecting data method used in this research was case study approach. Research instruments that supported this research were Handphone, stationary and researcher herself. The result itself showed that norm values within KidungMonani teach us to always respecting nature and local prosperity. Social responsibility had already been carried out by the company indicated by social activities and public facilities both for workers as well as for the locals. Waste management process and its reporting has beed carried out according to the applicable rules.